Identity Management with Biometrics - Bock, Lisa (Packt Publishing, 2020)
Work with common biometrics such as face, fingerprint, and iris recognition for business and personal use to ensure secure identification and authentication for fintech, homes, and computer systems Key Features Explore the next iteration of identity protection and overcome real-world challenges Understand different biometric use cases to deploy a large-scale biometric system Curated by renowned security ambassador and experienced author Lisa Bock Book Description Biometric technologies provide a variety of robust and convenient methods to securely identify and authenticate an individual. Unlike a password or smart card, biometrics can identify an attribute that is not only unique to an individual, but also eliminates any possibility of duplication. Identity Management with Biometrics is a solid introduction for anyone who wants to explore biometric techniques, such as fingerprint, iris, voice, palm print, and facial recognition. Starting with an overview of biometrics, you'll learn the various uses and applications of biometrics in fintech, buildings, border control, and many other fields. You'll understand the characteristics of an optimal biometric system and then review different types of errors and discover the benefits of multi-factor authentication. You'll also get to grips with analyzing a biometric system for usability and accuracy and understand the process of implementation, testing, and deployment, along with addressing privacy concerns. The book outlines the importance of protecting biometric data by using encryption and shows you which factors to consider and how to analyze them before investing in biometric technologies. By the end of this book, you'll be well-versed with a variety of recognition processes and be able to make the right decisions when implementing biometric technologies. What you will learn Review the advantages and disadvantages of biometric technology Understand the characteristics of an optimal biometric system Discover the uses of biometrics and where they are used Compare different types of errors and see how to tune your system Understand the benefits of multi-factor authentication Work with commonly used biometrics such as face, fingerprint, and iris Analyze a biometric system for usability and accuracy Address privacy concerns and get a glimpse of the future of biometrics Who this book is for Identity Management with Biometrics is for IT managers, security professionals, students, teachers, and anyone invo...